General overview of geotechnical monitoring used in construction - Shakhmov , Жанболат; Serigzhan , Бақытгүл (Рroblems of engineering and professional education, 2023)
The article briefly overviews available in the form of General monitoring of construction, detailed information on the specific geotechnical monitoring, principal, action, provides information about the development foreign practice monitoring.